Formación técnica en instalaciones eléctricas Luz Led y su incidencia en el rendimiento académico de los estudiantes del Colegio Fiscal de bachillerato Simón Bolívar Parroquia Tarqui, Cantón Guayaquil, Provincia del Guayas - Briones García, Segundo Efren (2019)
LED lighting (Light Emitting Diode) can be considered a new lighting technology that presents numerous benefits with respect to the different types of lighting found in the market. LED luminaires consume approximately 50% less energy than traditional lamps, have an approximate lifespan of 100,000 hours (6 times more than traditional sodium lamps), the color temperature it emits is whiter and more pleasing to the eyes , does not have toxic elements and pollutants that would cause damage to the environment. Street lighting is a subject of special interest in all countries of the world since it represents a large portion of energy consumption, and its proper use ensures safety for pedestrians and drivers. Through history, various types of electrical installations have been invented, always in order to provide illumination of the various places that any human being can inhabit. The initial illumination of the story was that of fire, and this has been transformed until reaching some types of more sophisticated bulbs with improved properties, which will be defined and explained in chapter four.